2022
DOI: 10.3389/fendo.2022.1000919
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty and microbiota: The role of the sex hormone–gut microbiome axis

Abstract: Puberty is a critical phase of life associated with physiological changes related to sexual maturation, and represents a complex process regulated by multiple endocrine and genetic controls. Puberty is driven by hormones, and it can impact the gut microbiome (GM). GM differences between sex emerge at puberty onset, confirming a relationship between microbiota and sex hormones. In this narrative review, we present an overview of precocious pubertal development and the changes in the GM in precocious puberty (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 95 publications
1
13
0
1
Order By: Relevance
“…The examination of gut microbiota profiles across adolescence and adulthood reveals a decline in Bifidobacteriaceae levels with advancing age. Puberty onset is marked by an increased abundance of Firmicutes and Clostridiales , accompanied by a concomitant decrease in Bacteroidales , as elucidated by Calcaterra et al in 2022 [ 59 ]. Post-pubertal development introduces significant distinctions, particularly in teenage girls, where Ruminococcaceae and Lachnospiraceae species increase, while Bacteroidales and Streptococcus decrease.…”
Section: Resultsmentioning
confidence: 99%
“…The examination of gut microbiota profiles across adolescence and adulthood reveals a decline in Bifidobacteriaceae levels with advancing age. Puberty onset is marked by an increased abundance of Firmicutes and Clostridiales , accompanied by a concomitant decrease in Bacteroidales , as elucidated by Calcaterra et al in 2022 [ 59 ]. Post-pubertal development introduces significant distinctions, particularly in teenage girls, where Ruminococcaceae and Lachnospiraceae species increase, while Bacteroidales and Streptococcus decrease.…”
Section: Resultsmentioning
confidence: 99%
“…This also includes better understanding how to restore physiologic levels of hormones in the midst of pathology. Hormone modulation is also critical in the treatment of conditions ranging from delayed puberty to gender dysphoria ( 39 – 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota, largely passed on from mother to child, has been shown to influence both metabolism and the production of certain hormones. Work on causes and treatment of precious puberty, for example, has examined the role of microorganisms ( 39 ).…”
Section: Hormones During Pubertymentioning
confidence: 99%
“…Bidirectional interactions between the gut microbiome and the sex hormones have been observed in various endocrine-related diseases. 7 , 8 , 9 Recent studies have shown that the gut microbiota can influence sex hormones and obesity-dependent perturbation of mice and rats. 10 , 11 Changes in the gut microbiome and associated metabolome have also been observed in girls with PPP and CPP.…”
Section: Introductionmentioning
confidence: 99%